IMPLEMENTATION OF THE USE E-CRM IN IMPROVING OPERATIONAL EFFICIENCY AND PROFITABILITY AT GALLERYPARFUME WEB-BASED - Syahillah, Bella; Irawati, Novica; Dewi, Muthia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
Abstract: Gallery Parfume Shop is a business engaged in cosmetics located on Jalan Merdeka, Simpang Empat, Kec. Tanjung Tiram, Kab. Batu Bara, North Sumatra. In the procedures and management of sales management at Gallery Parfume is still done manually, the reports are still recorded in notes the impact of this is that Gallery Parfume has difficulty in evaluating their sales performance, identifying market trends, and planning effective sales strategies and also difficulty building loyalty. Therefore, a system is needed, by implementing E-CRM at Gallery Parfume can get new customers, improve customer relationships, and retain customers, which will ultimately create customer loyalty and to measure the increase in profitability resulting from the use of E-CRM into a web-based application so that it will later facilitate increasing sales, customer loyalty, and saving operational costs. The method used to collect and analyze this research data is a qualitative method. It is expected that through this web application it can also build a database to make it easier for Gallery Parfume to search for data and reports.Keywords: consumers; e-crm; stores Abstrak: Toko Gallery Parfume merupakan usaha yang bergerak dibidang kosmetik yang berada dijalan Merdeka, Simpang Empat, Kec. Tanjung Tiram, Kab. Batu Bara, Sumatera Utara. Dalam prosedur dan manajemen pengelolaan penjualan di Gallery Parfume masih dilakukan secara manual, laporan nya masih tercatat di notes dampak dari hal tersebut gallery Parfume kesulitan dalam mengevaluasi kinerja penjualan mereka, mengidentifikasi tren pasar, dan merencanakan strategi penjualan yang efektif juga kesulitan membangun loyalitas. Maka dengan hal itu diperlukan sebuah sistem, dengan menerapkan E-CRM di Gallery Parfume dapat memperoleh pelanggan baru, meningkatkan hubungan dengan pelanggan, dan mempertahankan pelanggan, yang pada akhirnya akan terciptanya loyalitas pelanggan dan untuk mengukur peningkatan profitabilitas yang dihasilkan dari penggunaan E-CRM kedalam bentuk aplikasi berbasis web agar nantinya memudahkan dalam peningkatan penjualan, loyalitas pelanggan, dan penghematan biaya operasional. Metode yang digunakan untuk mengumpulkan dan menganalisis data penelitian ini dengan metode kualitatif. Diharapankan melalui aplikasi web ini juga dapat membangun database guna memudahkan Gallery Parfume dalam mencari data dan laporan.Kata Kunci: e-crm; konsumen; toko